Development of Interactive Media Based on Articulate Storyline to Enhance Student Interest at Junior High School on The Pressure of Substance’s Material - Albahy, Azmy Afif; Setiawan, Agung Mulyo (Journal of Disruptive Learning Innovation (JODLI), 2022)
Decreased student learning interest in the pressure of substance material is influenced by less interactive of learning media. The interactive media that we developed is based on articulate storyline application for junior high school’s student. The ADDIE (Analyze, Design, Development, Implementation, and Evaluation) model is used to develop this product. The results were increasing value in the pre-test 41,4 to post-test 54,5. Then the result of the t-test analysis obtained a significance value of 0,001<0,05. In addition, the percentage of the descriptive analysis shows that the majority of students were 'interested' in the interactive media is 76.66%. Thus, we get the conclusion that the development of interactive media based on Articulate Storyline is able to increase the student interest at junior high school in the pressure of substance material.